Practical considerations In antihistamine selection (Canadian Dermatology Today, 2022)
Antihistamines are medications that are used by dermatologists for the labelled indications of urticaria and IgE mediated allergies. They may also be used off-label for conditions including, but not limited to, mast cell-mediated diseases and pruritus of any type.With so many antihistamines available in Canada, it can be hard to choose which one to recommend or prescribe. With a focus on oral H1 antihistamines, the ones primarily used in dermatology, this review will explore and provide a practical overview to help physicians select ideal antihistamines for each patient based on their similar and unique characteristics.